(3SDGd aj (B" (3Gdfbd(B"s - (3CHj GdajV eMeO Hf eMeO Hf eMeO GHf YHO GdQGRb, GdSjO eQJVj GdMSjfj GdRHjOj,J (B1205 (3g` s
(3ChdgG (B:s
(3SDGd ai (B" (3Gdfbd(B" (3bGd GdRHjOi (B: (3Gdfbd eG jDcd HYO GdTQH hai GdbGehS (B: (3JQLjM GdaJM , hfSH def Ve GdNWC hYdjg agd Ydi HGd SjOfG TYQ JVef daXI Gdfbd s
(3BNQgG (B:s
(3hbGd CjVkG (B: (3cCS UHhM CYXJc aVdJgG ca MHjH hGdfbd ef bHd s
(3Vef eLehY , JQJjHgG (B: (3ef U (B194 - (3U(B194s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B70s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B2 s
(3eUOQ GbJfGA GdCUd (B:s
(3GdNRGfI GdYGeI (B_ (3GdQHGW (B(310(3O(B) s
Keywords: (3GddZIs